Til debt do us part : the enforceability of council´s country-specific recommendations under the excessive deficit procedure - Mesquita, António Gonçalves Porto Pinto de (2019)
Under Article 126 TFEU “Member States shall avoid excessive government deficits”. Member States are still in charge of their own budgetary policies, but they are still under the scope of the Treaties. Paragraph 7 of Article 126 states that “Where the Council decides, in accordance with paragraph 6, that an excessive deficit exists, it shall adopt, without undue delay, on a recommendation from the Commission, recommendations addressed to the Member State concerned with a view to bringing that situation to an end within a given period. Subject to the provisions of paragraph 8, these recommendations shall not be made public.” The changes brought by recent pieces of legislation reinforced the enforceability given to Recommendations on the matter of Economic and Monetary Integration. The Nature of Recommendations was addressed by the ECJ in Grimaldi and in Altair Chimica. It was there stated that Recommendations might carry legal enforceability, and that their content should be interpreted regarding its execution. It is my understanding that the current legal framework regarding Recommendations, more specifically Recommendations made under an Excessive Deficit Procedure, should be revisited in order to answer the questions of their enforceability. The answers to these questions are crucial pieces of the puzzle in which the Economic and Monetary Governance of the European Union entrenched in. As the time passes and more procedures of this kind come to their final stages, the more likely it is to a Member State or its Courts to challenge such Recommendations enforceability. This is why I believe it is relevant to revisit the question regarding Recommendations in order to make some sense of what really is the corrective arm of the Stability and Growth Pact.